Pemahaman Guru: Miskonsepsi Guru Mata Pelajaran Ilmu Pengetahuan Alam MTs terhadap Konsep Pembelajaran Berdiferensiasi - Ansori, Achmad Zanuar (Balai Diklat Keagamaan Surabaya, 2024)
The implementation of the Independent Curriculum in islamic schools brings a number of consequences, including the use of differentiated instruction. The concept of differentiated instruction is something new for teachers. This allows misconceptions to occur even though the teacher has obtained previous information. This article aims to find out the misconceptions of Islamic Junior High Schools sciences teachers regarding the concept of differentiated instruction. The respondents for this research were 35 participants of Implementation of Independence Curriculum training in science subjects. Data obtained through a questionnaire using Gform. The data was then processed using percentage techniques and described. The research results show that the overall value of misconceptions about the concept of differentiated instruction is 3.23, a medium category approaching high.